Gonorrhea in the Russian Federation: incidence, active case detection and laboratory diagnostics - Elena V. Bogdanova; Nikita Yu. Nosov; Xenia I. Plahova (Vestnik Dermatologii i Venerologii, 2025)
Background. Gonorrhea is a possible cause of pelvic inflammatory complications, reproductive health disorders and adverse pregnancy outcomes. The problem of gonococcal antimicrobial resistance remains actual.